Applying Standardized Rubrics for Assessing the Instructional Competence of Elementary School Teachers (EST) in Pakistan - Haider, Zubair; Hameed, Qasim; Ameen, Salma (Advances in Social Sciences Research Journal, 2015)
The current study examines the Elementary School Teachers’ (ESTs) instructional competence through standardized rubrics developed under guidance of Government of Pakistan and UNESCO. The main purpose of this research was to explore the current position of competencies of ESTs, to evaluate the various competencies of ESTs described in the National Professional Standards for Teachers in Pakistan and advocate certain measures to improve the competencies and evaluation mechanism of ESTs. The population of the study comprised of male and female ESTs working in government schools located in urban and rural areas of district Lodhran, Punjab Pakistan. To conduct the observational survey 225 ESTs were selected randomly. An observational checklist was made on recommended grounds of teacher accreditation by Policy and Planning wing of Ministry of Education, Pakistan and UNESCO. The Statistical Package for Social Sciences (SPSS version 19) was utilized to analyze the collected data. A number of descriptive statistics including Chi Square, mean and percentage were calculated. The study concludes that most of ESTs were found week in various teaching competencies.